Environmental liabilities, an analysis of importance. Case of the San Miguel de Sarampión community, Bolívar – Ecuador - Cobeña-Navarrete, Hugo (2023)
The objective of this study was to determine the importance of the existing environmental liabilities in the Sarampión micro-basin of the San Miguel de Sarampión community of the Bolívar canton, province of Manabí – Ecuador. The methodology was applied which included field visits to identify and georeference environmental liabilities, these were recorded in the standardized record instrument; Subsequently, the level of importance of environmental liabilities on the receiving body (Measles estuary) was established. The results indicate that there are 20 environmental liabilities, with waste accumulation persisting in 12 points; Also, two crop areas were identified on the bank of the estuary, two direct discharge points of residual water, two areas of obstruction of the estuary channel, an obstruction of the estuary bed and a cattle corral near the channel. In summary, it was obtained that 12 of the identified environmental liabilities have moderate importance, while 8 maintain high importance. In conclusion, the identified environmental liabilities denote an environmental deterioration of considerable importance, making it imperative that preventive actions be implemented to improve both the environment and the quality of life of the residents of the studied area.